Cutaneous IgA subclasses in dermatitis herpetiformis and linear IgA disease. - Wojnarowska, F; Delacroix, D; Gengoux, P (1988)
The subclasses of the cutaneous IgA were studied in 8 patients with dermatitis herpetiformis and 4 with linear IgA disease. The cutaneous IgA in dermatitis herpetiformis consisted of both IgA1 and IgA2, although IgA1 predominated. This demonstrated that the IgA is polyclonal and may be both mucosal and blood derived. The IgA in linear IgA disease was exclusively IgA1, confirming previous work, and suggesting that mucosal IgA may not make a major contribution to the skin deposits.